7th International Advances in Applied Physics and Materials Science Congress & Exhibition (APMAS 2017) Guest Editorial - Sahiner, Mehmet Alper; Oral, Ahmet Yavuz M. (Elsevier Ltd, 2017)
[No abstract available]
7th International Advances in Applied Physics and Materials Science Congress and Exhibition, APMAS 2017 -- Fethiye -- 164972
Keywords: Applied materials; Applied physics; Material science